DESIGN AND PERFORMANCE TEST OF A CABINET TYPE DRYER FOR DRYING BREADFRUIT CHIPS: A CASE STUDY OF THE SUMBER REJEKI PURWOSARI FARMERS GROUP, SEMARANG CITY - Apriandi, Nanang; Kristiawan, Timotius Anggit; Herlambang, Yusuf Dewantoro; Supandi, Supandi; Abidin, Zainal; Wibowo, Andryana Dwiandara (Journal of Mechanical Engineering and Applied Technology, 2023)
This study aims to design and build a cabinet-type breadfruit chips dryer powered by liquefied petroleum gas (LPG) and to assess the dryer's characteristics, particularly by observing the temperature and relative humidity (RH) variables in the drying chamber. This characteristic data is critical for forecasting the dryer's ability during drying. The experimental approach was carried out in three stages: design, assembly, and testing without a drying load under two process conditions, charging and discharging. The testing time is 150 minutes, with the charging procedure taking 70 minutes and the discharging process taking 80 minutes. In general, the distribution of temperature and RH on each shelf in the drying chamber is consistent, both during the charging and discharging processes. In the charging-discharging process, the average temperature of the drying room is 45.39 C with a RH of 40.99%, while the plenum room average temperature is 77.02 C.